VIABILITY OF CONVERTING THE GREEN SPACES OF 48 HOSPITAL CAMPUSES IN PORTUGAL INTO THERAPEUTIC GARDENS BASED ON THEIR USABILITY, TREE COVER AND PROXIMITY - Bruno Gonçalves Martins; Frederico Meireles Rodrigues (Finisterra - Revista Portuguesa de Geografia)
Therapeutic Gardens are green spaces focused on improving mental and physical healing, as well as provide wellbeing. Thus, these green spaces can constitute an important extension of the hospital space, complementing or even adding new functions to healthcare institutions. This article aims to contribute to the assessment of the conversion of current green spaces and permeable areas in 48 portuguese public hospital campuses into TG through the evaluation of 1) the current usability of green spaces, in order to assess whether the existing green spaces have structures, furniture, etc. that allow their use or whether it is necessary to construct them; 2) the existing tree cover in green spaces, as it is structural, allows to have a mature garden more quickly and provide more ecosystem services and 3) the  proximity to hospital buildings with the aim of evaluating part of the direct access required by the TG. We conclude on the lack of usable green spaces and tree cover in most hospital campuses, which would imply a greater effort to reconvert these spaces. However, the existing green spaces and tree cover are located close to the hospital buildings, which also makes the conversion possible. We also noticed a lack of specifications for the construction of TG, mainly for specialized hospitals such as those for children and older adults, and also for evaluating green spaces quality in hospitals.